Comparison of microRNA expression in high-count monoclonal B-cell lymphocytosis and Binet A chronic lymphocytic leukemia - Felipe Magalhães Furtado; Priscila Santos Scheucher; Bárbara Amélia Santana; Dalila Lucíola Zanette; Rodrigo do Tocantins Calado; Eduardo Magalhães Rego; Daniel Mazza Matos; Roberto Passetto Falcão (Revista Brasileira de Hematologia e Hemoterapia)
Abstract Background Evidence suggests that monoclonal B-cell lymphocytosis precedes all chronic lymphocytic leukemia cases, although the molecular mechanisms responsible for disease progression are not understood. Aberrant miRNA expression may contribute to the pathogenesis of chronic lymphocytic leukemia. The objective of this study was to compare miRNA expression profiles of patients with Binet A chronic lymphocytic leukemia with those of subjects with high-count monoclonal B-cell lymphocytosis and healthy volunteers (controls). Methods Twenty-one chronic lymphocytic leukemia patients, 12 subjects with monoclonal B-cell lymphocytosis and ten healthy volunteers were enrolled in this study. Flow cytometry CD19+CD5+-based cell sorting was performed for the chronic lymphocytic leukemia and monoclonal B-cell lymphocytosis groups and CD19+ cells were sorted to analyze the control group. The expressions of miRNAs (miR-15a, miR-16-1, miR-29b, miR-34a, miR-181a, miR-181b and miR-155) were determined by quantitative reverse transcriptase polymerase chain reaction (qRT-PCR). Results Significant differences between the expressions in the chronic lymphocytic leukemia and monoclonal B-cell lymphocytosis groups were restricted to the expression of miR-155, which was higher in the former group. A comparison between healthy controls and monoclonal B-cell lymphocytosis/chronic lymphocytic leukemia patients revealed higher miR-155 and miR-34a levels and lower miR-15a, miR-16-1, miR-181a and miR-181b in the latter group. Conclusions Our results show a progressive increase of miR-155 expression from controls to monoclonal B-cell lymphocytosis to chronic lymphocytic leukemia. The role of miR-155 in the development of overt chronic lymphocytic leukemia in individuals with monoclonal B-cell lymphocytosis must be further analyzed.